Associations between metal exposure and metabolic syndrome: exploring the mediating role of biological ageing among US adults - Liuyan Zheng; Xinyue Lu; Suping Luo; Jianhui Guo; Xingyan Xu; Le Yang; Mingjun Chen; Shaowei Lin; Xiaoxu Xie; Huangyuan Li; Siying Wu (Diabetology & Metabolic Syndrome)
Abstract Background The relationship between mixed metal exposure and metabolic syndrome (MetS) remains controversial, and the underlying mechanisms of this relationship are not yet fully understood. Objective We evaluated the association between urinary metals and MetS and investigated the potential mediating effect of ageing. Methods This study utilized National Health and Nutrition Examination Survey (NHANES) data from 1999 to 2018 and included 11,541 adults aged 20 years and above. We explored the association between urinary concentrations of nine metals and MetS using weighted quantile sum (WQS) regression, grouped weighted quantile sum (GWQS) regression, and Bayesian kernel machine regression (BKMR). In addition, various methodologies have been used to assess biological ageing, encompassing the examination of cellular senescence through the evaluation of telomere length, as well as a comprehensive evaluation of overall body ageing through the determination of biological age. The contribution of biological ageing to the association between urinary metals and MetS was investigated in a mediation analysis. Results After adjusting for confounders, the WQS and GWQS analyses found positive and negative correlations between metal exposure and MetS, and the main metals affecting MetS risk were cadmium (Cd) and lead (Pb), respectively. A positive relationship was found between exposure to mixed metals and the risk of MetS in the BKMR results. Mediation analysis showed that ageing biomarkers, including biological age and telomere length, mediated 68.43% and 12.05% of the association between metal exposure and MetS, respectively. Biological ageing may play a major role in the association between mixed metal exposure and MetS. Cd contributed the most to the positive association, indicating that priority control measures may be necessary to reduce the risk of MetS related to Cd exposure. Significance The findings of this study could contribute to the advancement of targeted measures for metal precautions, ultimately mitigating the incidence of metabolic syndrome. Impact statement This research employed multipollutant models including WQS regression, GWQS and BKMR to evaluate the combined effects of various metal exposures on the risk of developing MetS based on a nationally representative large cross-sectional study. In addition, this research investigated biological aging by conducting a comprehensive assessment of biological age and telomere length. Our goal is to understand its potential mediating effect on metal exposure and the occurrence of metabolic syndrome. The insights gained from this study could provide valuable hints for future mechanistic research in this field.